IDENTIFIKASI HUTAN MANGROVE AIR TAWAR SEBAGAI GREEN ASSETS UNTUK INCOME GENERATING DESA YANG BERKELANJUTAN - Hudaya, Muhammad; Nor, Wahyudin; Kadir, Kadir; Nordiansyah, Muhammad; Yuliastina, Mellani (Universitas Islam Malang, 2025)
Village tourism has significant potential to enhance Village Original Revenue (PADes), particularly through the optimization of local assets and community involvement. Tatah Makmur Sub-district possesses natural resources that have not been fully utilized, notably a unique fresh-water mangrove forest. This community service activity aims to explore the tourism potential in the area as an effort to increase PADes. The partners involved are the village government and local communities. A participatory approach based on Participatory Rural Appraisal (PRA) was employed, including tourism potential surveys, green tourism site mapping, focused group discussions (FGDs), and training focused on tourism income potential and the importance of preserving village green assets. The results identified two promising green tourism sites: the fresh-water mangrove forest in Tatah Bangkal Tengah Village and river punting tourism in Pandan Sari Village. Moreover, the pohon rambai tree dominating the mangrove area can be developed into environmentally friendly ventures such as ecotourism and honeybee farming. This activity also contributes to community empowerment through the establishment of tourism awareness groups (Pokdarwis), tourism management training, and promotion of transparent village financial planning. With government support and active community participation, Tatah Makmur is expected to develop into a sustainable tourism destination that improves local welfare